Quantification and study of anomalous trends of annual rainfall in the state of Bahia between 1980 and 2019 - Silva, Eulalia Pessin; Aquino, David Santiago (Seven Editora, 2023)
Water is a natural resource of extreme relevance for human activities, as well as for the maintenance of biodiversity on Earth. In the circulation of water on the planet, described by the hydrological cycle, precipitation stands out, which allows the return of part of the fresh water present in the atmosphere to the earth's surface, being, therefore, a stage of the cycle with direct implications for the availability of this resource. In the context of climate change, it is necessary to pay attention to possible trends of changes in rainfall, especially regarding the possibilities of extreme events, such as abundance of rainfall, favoring floods, or even long periods of scarcity, which can compromise the availability of water.  Some studies have identified these rainfall trends in localities of the Brazilian Northeast. However, there is still no study, available in the literature, covering the entire state of Bahia. Thus, this plan estimated the occurrence of anomalies related to precipitationinthe state of Bahia. To this end, the  Rainfall Anomaly Indexes (IAC) were used, which were calculated annually for 24 rainfall stations distributed in the state.  We used the monthly precipitation data recorded in theseseasons for the historical series from January 1980 to December 2019.  An amount of 671 anomaly indices was determined, being 338 negative results, which express drier periods or with a lack of rainfall, and 333 positive anomalies, which indicate wetter periods in relation to the historical average.  The variations of these indices are described, according to the corresponding seasons, by means of a graphic study. Finally, maps of the spatial distribution of anomalies throughout the state of Bahia are elaborated. DOI:https://doi.org/10.56238/devopinterscie-273